Sports foods are not all they shake up to be. An audit of formulated supplementary sports food products and packaging in Australian retail environments - Chapple, Celeste I.; Russell, Catherine G.; Burnett, Alissa J.; Woods, Julie L. (Frontiers in Nutrition, 2023)
Objective To determine store availability, total number of products, and types of Formulated Supplementary Sports Foods in Australia, along with their stated nutrition content, sweeteners added, total number, and type of claims displayed on the packaging. Design A cross-sectional, visual product audit of mainstream retailers. Setting Supermarkets, pharmacies, health food stores, and gym/fitness centres. Results A total of 558 products were captured in the audit, 275 of which displayed the correct mandatory packaging attributes. Three categories of products were identified, based on the dominant nutrient. Only 184 products appeared to display the correct energy value based on the listed macronutrient content (protein, fat, carbohydrate, dietary fibre). The stated nutrient content was highly variable across all product subcategories. Nineteen different sweeteners were identified, with most foods containing only one (38.2%) or two (34.9%) types. The predominant sweetener was stevia glycosides. Packages displayed multiple claims, with a maximum of 67 and minimum of 2 claims. Nutrition content claims were most frequently displayed (on 98.5% of products). Claims included regulated, minimally regulated and marketing statements. Conclusion Sports food consumers should be provided with accurate and detailed on pack nutrition information, to ensure informed choices are made. However, this audit showed multiple products which did not conform to current standards, appeared to provide inaccurate nutrition information, contained multiple sweeteners, and displayed an overwhelming number of on-pack claims. The increase in sales, availability, and products available in mainstream retail environments, could be impacting both intended consumers (athletes), and general non-athlete population. The results indicate underperformance in manufacturing practices which preference marketing over quality and stronger regulatory approaches are needed to protect consumer health and safety, and to prevent misleading consumers.